Thermal effect and oxygen-enriched effect of N2O decomposition on soot formation in ethylene diffusion flames. (1st December 2022) - Li, Yueh-Heng; Hsu, Chung-Hao; Lin, Po-Hung; Chen, Chun-Han
Highlights: Effect of N2 O decomposition on soot formation in N2 O/C2H4 flame was examined. Thermal effect of N2 O decomposition on soot formation increased with the R value. The oxy-enrichment effect on soot formation increased gradually. Soot formation and oxidation rate rebalances under the N2 O decomposition effect. Abstract: This study experimentally investigated the effect of nitrous oxide (N2 O) decomposition on soot formation in N2 O/ethylene diffusion flames. The effect of N2 O decomposition on the soot formation mechanism was examined in three oxidation cases (Cases Case I–III). In Case I, N2 O was used as the oxidant; in Case II, an oxygen-enriched N2 /O2 mixture (67 % N2 + 33 % O2 ) was used as the oxidant; and in Case III, standard air (79 % N2 + 21 % O2 ) was used as the oxidant. A triple-port burner was used to generate diffusion flames with various R (ratio of the oxidizer flow velocity to the fuel flow velocity) values ( R = 0–6). The soot concentration was measured through laser-induced incandescence, and the soot temperature was determined using two-color pyrometry. The measured soot temperatures increased significantly due to the thermal effect in the upstream position of the N2 O/C2 H4 flames. The oxygen-enrichment effect on soot formation increased gradually from 10 % to 60 % as R increased from 0.5 to 6. The integration of the soot concentration along the flame length revealed that the soot formation rate and soot oxidation rate might rebalance under the N2 O decomposition effect.